The effectiveness of emotion regulation therapy (ERT) on improving depression, anxiety and stress in patients with myocardial infarction - Javadi, Bahareh; Davazdahemamy, Mohamad Hasan; Gheidari, Mohmad Ismail; Noori, Mohamad (Researcher Bulletin of Medical Sciences, 2018)
Background: Among the cardiovascular diseases, myocardial infraction is one the main cause of mortality around the world. People with myocardial infarction are significantly more likely to suffer from psychological problems, such as depression, anxiety and stress. Therefore, psychological interventions can help their routine treatment. The purpose of this study was to determine the effectiveness of emotional regulation therapy on depression, anxiety and stress in patients with myocardial infarction. Methods: In this single-case design, 5 patients with myocardial infarction referred to the Taleghani Hospital were selected using convenience sampling method. They received eight sessions of emotional regulation psychotherapy. These patients were evaluated by anxiety, stress, and depression scale (DASS-21) before starting treatment and after each session. Results: The results showed that emotional regulation therapy significantly reduced depression, anxiety and stress in patients with myocardial infarction. Discussion: According to the findings of this study indicating the effectiveness of emotional regulation therapy on depression, anxiety and stress in patients with myocardial infarction, this treatment can be used as part of a comprehensive treatment process for these patients.